Effects affecting ammonia removal in synthetic wastewater by locally isolated Rhodobacter sp strain A1 - Shalehuddin, Masturah; Shahir, Shafinaz; Ibrahim, Zaharah; Hasmoni, Siti Halimah (BIORE Scientia Publisher, 2024)
This research focused on the effects affecting ammonia removal in synthetic wastewater by Rhodobacter sp. strain A1 using one factor at a time method (OFAT). Rhodobacter sp. strain A1 are able to remove ammonia from synthetic wastewater due to its ability to assimilate ammonia. The ammonia removal experiment was conducted under different factors; Rhodobacter sp. strain A1 inoculum size (2%, 4%, 6%), incubation temperature (20°C, 25°C, 30°C, 37°C, 40°C), initial pH of synthetic wastewater (5,6,7,8,9) and initial NH4Cl concentration (5 mg/L, 10 mg/L, 15 mg/L) for four days of incubation period. Then, the solution was tested using Nessler reagent which will produce yellow colour when it reacts with ammonia. The intensity of colour is proportional to the ammonia concentration. This experiment was followed by ammonia quantitative analysis via spectrophotometer at 425 nm. The results obtained were then calculated to get the percentage of ammonia removal by PNSB. The result revealed that the bacterium can achieved 97.90 % efficiency of total ammonia removal at optimum growth condition with 6% of inoculum size, incubation temperature at 30°C and initial pH 7. As a conclusion, this Rhodobacter sp. strain A1 can therefore serve as a good candidate in wastewater treatment for ammonia removal.